2021
DOI: 10.1177/10776990211017243
|View full text |Cite
|
Sign up to set email alerts
|

Protest News and Facebook Engagement: How the Hierarchy of Social Struggle Is Rebuilt on Social Media

Abstract: This content analysis expands protest paradigm research, examining the relationship between Facebook user engagement and newspaper protest coverage. Stories not posted to social media housed more negative frames that delegitimized protesters. For select protests, Facebook users engaged more with articles with legitimizing content, suggesting users, like journalists, follow a paradigm that legitimizes some protests and marginalizes others. We discuss these implications and consider how engagement plays a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…We can expect that this prioritization will play out in coverage of all kinds, and considering the rise in protest activity over the past two decades that has created perpetual and concurrent attention to social movements, we can also anticipate that some protests will be prioritized and treated differently than others for reasons other than the movement's perceived threat to destabilize the status quo. The comparative framework provided by the hierarchy of social struggle, which we have extended to social media (Harlow and Brown 2021), encourages us to explore how media systems and societies have differentially prioritized various social struggles. This comparative approach offers opportunities for quantitative and qualitative researchers to lean into the application of critical theories by interrogating intersecting power systems.…”
Section: Reimagining a More Critical Paradigmmentioning
confidence: 99%
“…We can expect that this prioritization will play out in coverage of all kinds, and considering the rise in protest activity over the past two decades that has created perpetual and concurrent attention to social movements, we can also anticipate that some protests will be prioritized and treated differently than others for reasons other than the movement's perceived threat to destabilize the status quo. The comparative framework provided by the hierarchy of social struggle, which we have extended to social media (Harlow and Brown 2021), encourages us to explore how media systems and societies have differentially prioritized various social struggles. This comparative approach offers opportunities for quantitative and qualitative researchers to lean into the application of critical theories by interrogating intersecting power systems.…”
Section: Reimagining a More Critical Paradigmmentioning
confidence: 99%
“…journalists use a specific set of frames to cover activists and social movements, most of which position social protests outside the mainstream.” Recent studies posit that in some cases, news media can amplify and generate public support for protest (Lee, 2014), or that the protesting group’s tactics (Boyle et al, 2012); community and media structures local to the protest (McCluskey et al, 2009); and/or social media engagement with posted news articles about the protest (Harlow & Brown, 2021) can affect whether and how the paradigm is present. Harlow and Brown (2021) observed that, while social media engagement can amplify the protesters’ goals and render news media coverage less paradigmatic over time, the overall “hierarchy of social struggle shows that the media . .…”
Section: The Protest Paradigm Race and Colorblindnessmentioning
confidence: 99%
“…A substantial empirical literature has consistently revealed problematic news framing in the coverage of Black Lives Matter (BLM) protests, with both national and local news sources highlighting riots, rather than the substantive issue focus of the protests (Leopold and Bell 2017; Mourão, Kilgo, and Sylvie 2018). Furthermore, one study showed that news organizations often avoid posting stories about antiracism protests to their Facebook pages—a practice suggesting that platform dynamics shape the visibility of public actions designed to highlight social inequalities (Harlow and Brown 2021). Despite some increases over time in newspaper coverage of racialized health disparities (Taylor-Clark et al 2007), a grim set of findings revealed that only 0.09 percent of U.S. newspaper articles addressed racialized health disparities (Amzel and Ghosh 2007).…”
Section: Literature Reviewmentioning
confidence: 99%